The MADS-box Transcription Factor PsMAD1 Is Involved in Zoosporogenesis and Pathogenesis of Phytophthora sojae - Lin, Long; Ye, Wenwu; Wu, Jiawei; Xuan, Mingrun; Li, Yufei; Gao, Jian; Wang, Yonglin; Wang, Yan; Dong, Suomeng; Wang, Yuanchao (Frontiers in Microbiology, 2018)
Transcriptional regulation is critical for plant pathogen development and virulence. MADS-box transcription factors belong to a highly conserved transcriptional regulator family in eukaryotic organisms that are involved in various important biological processes. Only one predicted MADS-box gene, PsMAD1, was identified in Phytophthora sojae, which was highly expressed during the sporangia and infection stages. To investigate its function, we generated PsMAD1 knockout mutants using the CRISPR/Cas9 system. Compared with the wild-type strain, the mutants showed no changes in vegetative growth, oospore production, or no differences in sensitivity to various abiotic stresses. Although sporangia production was normal, no zoospore release was detected in PsMAD1 mutants. Microscopy analyses revealed failure of cleavage of the cytoplasm into uninucleate zoospores in the mutants. In addition, the mutants showed reduced virulence in soybean. RNA-seq data indicated that PsMAD1 may regulate many zoospore development and infection associated genes. Thus, PsMAD1 may be a major regulator of P. sojae involved in zoosporogenesis and pathogenesis.